Plan de acción para Metro - Arbulu Carrasco, Daniela Ximena (2023)
Metro is a Peruvian supermarket chain that has been operating since 1992. It was created by the Wong family as an alternative for housewives, having as its main attribute its low prices. In 2007, the chain was sold to the Cencosud holding company with 100% of its shares. Currently, due to the preference of the public, Metro has 69 stores in Peru, being one of the main supermarkets in the country. However, over the years, Metro has been embroiled in a series of problems that have affected the reputation of the brand. Nowadays, Metro is involved in a severe reputational crisis due to a recent incident that occurred in Metro Chorrillos, the chain's first headquarters in history, when a video where two rodents can be seen walking through the area of refrigerated sausages and cheeses in front of customers went viral, causing discontent and public claim. Faced with this situation, the supervisory authorities reacted and acted quickly on the situation, keeping Metro in their sights. With the need to take action on this problem, efforts will be made to strengthen the imagen of Metro through an action plan. Additionally, there will be efforts to promote and communicate a space for collaboration and transparency with authorities. To achieve this, firstly, an external communication plan will be developed that targets the main stakeholders of the company. Secondly, a crisis manual will be created and communicated to Metro's internal audience in order to apprise employees about the process to follow in cases of crisis.